Integration of Total Quality Management in National Standards of Islamic Education - Putri, Sandy Aulia; Putri, Aisyah Gufron Liana; Jafar, Lili Septiani; Nasuah, Risma; Yudiawan, Agus (Institut Agama Islam Negeri Sorong, 2025)
This study aims to analyze the integration of Total Quality Management (TQM) principles in Islamic education policy documents issued by the Ministry of Religion, especially the National Standards of Islamic Education (NSIE) and the guidelines of the Internal Quality Assurance System (IQAS). The research approach uses a document-based descriptive qualitative method (library research), with content analysis techniques to assess the extent to which TQM principles, such as leadership, performance measurement, continuous improvement, stakeholder participation, and quality orientation, have been reflected in the policy. The results of the study show that the Ministry of Religion's document has emphasized leadership, performance measurement, and continuous improvement mechanisms, but the principles of external stakeholder involvement and overall quality culture are still limited. The analysis of the discussion emphasized that the integration of TQM in policies is progressive, but the effectiveness of its implementation depends on the capacity of institutions, the training of educators, and a more systematic mechanism of stakeholder engagement. This research provides implications for strengthening Islamic education policies, including the development of a quality culture based on Islamic values, improving student orientation, and providing technical guidance for the implementation of TQM in madrasas, Islamic boarding schools, and Islamic universities. The limitations of the research lie in the focus of document analysis, so that implementation practices in the field, perceptions of educators, and stakeholder responses are not explored directly. The next research recommendation is to evaluate the implementation of TQM empirically at the institutional level and develop a contextual and participatory quality management model.